Perencanaan Tenaga Kerja Unit Operasi & Pemeliharaan Bagian Keselamatan & Keamanan IT (Studi Kasus Terminal 3 Bandara Soekarno Hatta) - I Gede Indra Aryasa; Juliana, Mia; Sitanggang, Bryan Estavan Imanuel (JURNAL RISET DAN APLIKASI TEKNIK INDUSTRI, 2025)
Manpower planning is one of the keys to the success of a company in facing competition in business. One way to plan the company's workforce needs is to find out the workload currently being experienced by officers. The full-time equivalent (FTE) method is a method used to calculate the overall workload that can be used to perform workforce planning. The IT Safety & Security Division (SSIT) is currently experiencing high task completion time problems in the job description of checking all camera functions and preventive maintenance cameras. One of the causes of high task completion time is that the number of assets is too much compared to the number of workers. From the calculation using the full-time equivalent method, it is known that the FTE value for checking and preventive maintenance is 1.96 (Overload) if based on the calculation of shift assumptions / week and the FTE value for checking and preventive maintenance is 3.02 (Overload) if based on the calculation of the assumption of the needs of alternative solution officers with the addition of 8 shifts/week or 7 officer additions.